Direct discharge from the emergency department of simple stable injuries: a propensity score-adjusted non-inferiority trial. Issue 1 (14th April 2021) - Geerdink, Thijs H; Augustinus, Simone; Groen, Jasper J; van Dongen, Johanna M; Haverlag, Robert; van Veen, Ruben N; Goslings, J Carel
Abstract : Background: Recent studies suggest a large proportion of musculoskeletal injuries are simple stable injuries (SSIs). The aim of this study was to evaluate whether direct discharge (DD) from the emergency department (ED) of SSIs is non-inferior to 'traditional care' regarding treatment satisfaction and functional outcome, and to compare other patient-reported outcomes (PROMs), patient-reported experiences (PREMs), resource utilization, and adverse outcomes before and after DD. Methods: This trial compared outcomes for 11 SSIs 6 months before and after the implementation of DD protocols. Pre-DD, patients were treated according to local protocols. Post-DD, patients were discharged directly using removable orthoses, discharge leaflets, smartphone application, and telephone helpline. Participants received a 3-month postinjury PROM/PREM survey to assess treatment satisfaction (Visual Analog Scale, VAS), pain (VAS), functional outcome (four validated questionnaires), and health-related quality of life (HR-QoL; EuroQol-5D). Resource utilization included general practitioner (GP) visit (yes/no), physiotherapist visit (yes/no), return to work/school/sports (days), work/school absenteeism to visit hospital (yes/no), number of hospital visits, and follow-up X-rays. Other outcomes included missed injuries (additionally to SSI) and adverse outcomes (delayed union, non-union). Between-group differences were assessed using propensity score-adjusted regression analyses. Non-inferiority was assessed for satisfaction and functional outcome using predefined margins. Results: 348 (pre-DD) and 371 (post-DD) patients participated; 144 (41.4%) and 153 (41.2%) patients completed the survey. Satisfaction and functional outcome post-DD were non-inferior to traditional care. Mean satisfaction was 8.13 pre-DD and 7.95 post-DD (mean difference: −0.16, p=0.408). Pain, HR-QoL, GP/physiotherapist visits, and return to work/school/sports were comparable before and after DD. Work absenteeism was higher pre-DD (OR 0.110, p<0.001), as well as school absenteeism (OR 0.084, p<0.001). Post-DD, the mean number of hospital visits and X-rays reduced: −1.68 (p<0.001) and −0.26 (p<0.001). Missed injuries occurred once pre-DD versus twice post-DD. There were no adverse outcomes. Discussion: The results of this study confirm several SSIs can be discharged directly from the ED without compromising patient outcome/experience. Future injury-specific trials are needed to conclusively assess non-inferiority of DD. Level of evidence: II.